Case Report: B Lymphocyte Disorders Under COVID-19 Inflammatory Pressure - Taliani, Gloria; Follini, Elena; Guglielmetti, Lorenzo; Bernuzzi, Patrizia; Faggi, Alberto; Ferrante, Patrizia; Fronti, Elisa; Gerna, Laura; Leoni, Maria Cristina; Paolillo, Franco; Ratti, Giovanna; Ruggieri, Alessandro; et al. (Frontiers in Oncology, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infects humans through the angiotensin converting enzyme-2 (ACE-2) receptor expressed on many cells, including lymphocytes. In Covid-19 patients IL-6 is overexpressed and hyperactivated plasmacytoid lymphocytes are detected in peripheral blood film. We hypothesize that, due to the unpredictable interaction between the new virus and the B cell lineage of infected patients, a cascade of out of control events can ensue, capable of determining unexpected pathologic disorders involving such lineage. Here we report two cases of autoimmune hemolytic anemia (AIHA) and two cases of B-cell hematological malignancies developed or reactivated during acute SARS-CoV-2 infection. The temporal relationship of the events may suggest a potential causal relationship between SARS-CoV-2 infection and the hematopoietic disorders. We suggest that special attention should be paid to COVID-19 patients with underlining B cell lineage disorders.